2005
DOI: 10.1097/01.aids.0000194793.36175.40
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the intracellular accumulation of saquinavir in peripheral blood mononuclear cells by inhibitors of MRP1, MRP2, P-gp and BCRP

Abstract: Multiple drug efflux transporters are important in the intracellular accumulation of SQV in PBMC. If drug efflux contributes towards virological failure, then all contributing transporters will need to be inhibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 29 publications
(32 reference statements)
1
86
1
Order By: Relevance
“…Although tissue drug concentrations in the upper intestinal tract have not been investigated to date, formation of a viral reservoir is observed in GALT tissue isolated from the upper jejunum of HIV-infected subjects (6,31). Similarly to intestinal enterocytes, gut-associated lymphocytes also express several drug efflux (e.g., Pgp, BCRP, and MRP1, -2, -4, and -5) and uptake (e.g., OATP1A2, OATP3A1, and ENT1 and -2) transporters, which may be differentially expressed in HIV-1-infected and uninfected individuals and could affect the intracellular levels of ARVs achieved in this cellular compartment (16,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Although tissue drug concentrations in the upper intestinal tract have not been investigated to date, formation of a viral reservoir is observed in GALT tissue isolated from the upper jejunum of HIV-infected subjects (6,31). Similarly to intestinal enterocytes, gut-associated lymphocytes also express several drug efflux (e.g., Pgp, BCRP, and MRP1, -2, -4, and -5) and uptake (e.g., OATP1A2, OATP3A1, and ENT1 and -2) transporters, which may be differentially expressed in HIV-1-infected and uninfected individuals and could affect the intracellular levels of ARVs achieved in this cellular compartment (16,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are warranted to examine the role of MRP4 in ciprofloxacin handling by these cells and to determine whether it is as effective in other mammalian species, including humans. Because ciprofloxacin-resistant cells also overexpress Mrp2, we also suspect additional interferences, since this transporter confers resistance to several anticancer drugs (cisplatin, anthracyclines, vinca alkaloids, and methotrexate) and is detected in peripheral blood mononuclear cells (15). The long-term consequences of ciprofloxacin use on drug handling and other functions of phagocytic cells may therefore need to be addressed carefully in relation to efflux.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these transporters could be important modulators of the pharmacokinetics of these drugs by affecting their distribution in the body (van der Sandt et al, 2001;Huisman et al, 2002;Janneh et al, 2005Janneh et al, , 2007Anderson et al, 2006;Zastre et al, 2009). Studies have shown a relationship between intracellular concentrations of protease inhibitors in peripheral blood mononuclear cells and ABCC1 expression (Jones et al, 2001a;van der Sandt et al, 2001;Meaden et al, 2002;Janneh et al, 2005;Agarwal et al, 2007;Zastre et al, 2009). In addition, the efflux of emtricitabine (an NRTI) in lymphocytes by ABCC1 has been demonstrated (Bousquet et al, 2008a).…”
Section: H Atp-binding Cassette Subfamily C Transporters (Multidrug mentioning
confidence: 99%